Uji Eksperimental Efisiensi Panas Alat Pengering Surya Langsung Pasif Berbiaya Murah dengan Variasi Material Penutup Transparan - Kemas Muhammat Abdul Fatah; Indriyani; Ari Beni Santoso (P3M Politeknik Negeri Cilacap, 2022)
Indonesia should be able to provide inexpensive solar dryers due to the availability of sunlight all year round throughout the country. This study proposes a passive direct solar dryer as it is the simplest one to construct, with aluminum mesh sheets as a heat-absorbing material, and glass fiber as an insulating material. For the cost-effective transparent cover, this study proposes 0.8 mm clear polycarbonate (PC), 2 mm clear glass, and 2 mm clear acrylic. The experimental test results of the solar dryer model showed that the highest heat efficiency value for polycarbonate (PC) is 16%, whereas the heat efficiency value for glass and acrylic is 10% and 8%, respectively. Through these findings, the construction of solar dryers is simple and low cost by using glass fiber as insulation, aluminum mesh sheets as heat absorbers, and PC instead of thin glass as transparent covers.